HUBUNGAN EFIKASI DIRI DAN KETAHANAN KELUARGA DENGAN ADIKSI SMARTPHONE PADA REMAJA SMPN 57 JAKARTA - Aghna Alfafa Mamnunia (2023)
The phenomenon of smartphone addiction in adolescents continues to increase every year. Smartphone addiction is defined as smartphone addiction behavior that causes the sufferer to be unable to maintain normal daily life. Teenagers who experience smartphone addiction can experience academic problems, psychological problems, and have physical impacts. This study aims to determine the relationship between self-efficacy and family resilience with smartphone addiction in adolescents at SMPN 57 Jakarta. The study used the Chi Square test with a cross sectional approach, a sample of 207 adolescents and the sampling was carried out using a stratified simple random sampling technique. Data were obtained using the questionnaire General Self Efficacy Scale, Walsh Family Resilience Questionnaire, and Smartphone Addiction Scale Short Version. The results showed that there was a relationship between self-efficacy and smartphone addiction in adolescents which obtained a p-value of 0.008 (<0.05) and there was also a relationship between family resilience and smartphone addiction in adolescents which obtained a p-value of 0.041 (<0.05). Researchers suggest that adolescents can be more active in participating in positive activities so that they can increase self-efficacy, and families can strengthen relationships, so that adolescents do not need to look for happiness from outside by using smartphone.